On the possibility of applying modern design solutions of ocean-technical constructions for the Azov sea shelf - Zaiets, Anastasiia (Eastern-European Journal of Enterprise Technologies, 2016)
Achieving energy independence is one of the most important issues of modern Ukraine. Solution of this problem is impossible without the exploration of the shelf of the Azov-Black Sea basin; therefore development and design of ocean-technical constructions for the hydrocarbon raw materials exploration in the conditions of the Black and Azov Seas is the main step. In this article we examine selection of the architectural-construction type of an ocean technical construction, taking into account the ice loads, characteristic for the Azov Sea basin. A neural network analysis was perormed of the forecast of the thickness of ice in winter period and the ice loads on several types of constructions were calculated. As a result of the calculations it was revealed that under the considered conditions, the most suitable type of construction is an ice resistant stationary platform of gravitational type, which includes an extended structure with inclined front face at the level (depth) of sea of 8,0 m, and at the depth of 12,0 m is an extended structure with a combination of inclined sections and vertical parts of the columns on the front face. Performed calculations are also important from the point of view of the decrease of technological works and consumption of materials during construction, since we applied real physical values of ice formations, not the maximal ones registered over 100 years.